The Effect of Health Counseling on Pre-Elderly Knowledge Levels About Hypertension at RT 21 Glagahsari, Umbulharjo - Ayu Nursucita (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Hypertension is a condition that causes abnormalities in blood pressure that can interfere with other organ systems and can cause other diseases such as coronary heart disease and stroke. Hypertension is caused by a disturbance in the blood vessels which results in the supply of oxygen and nutrients carried by the blood being blocked to the body's tissues that need it. Hypertension has become a major problem in public health in Indonesia and in several countries in the world. One of the efforts to improve public health is through the application of a healthy lifestyle. This will be achieved if people get correct information about health either through electronic media or through counseling methods. The purpose of this community service activity is to determine the effect of health education on the level of pre-elderly knowledge about hypertension. The design method in this activity is Pre experimental design and the design is in the form of. One group pre-test-post-test. The population in this activity is 70 families, the sample size uses a minimum sample size of 30 families as the sample with the target of this activity being pre-elderly people aged 45-59 years. In measuring the level of knowledge, pretest and posttest questions were filled in with 15 questions each. The test group was given health education through lectures using leaflets with the door to door technique (from house to house). Results: Based on the statistical test using the Wilcoxon test, it is known that the Asymp value. Sig (2-tailed) is 0.000, because 0.000 <0.05, then according to the established hypothesis, it means that the health education method given regarding hypertension in the pre-elderly has been proven to increase pre-elderly knowledge compared to before health education was conducted. Conclusion: Health education has an effect on the level of knowledge of pre-elderly.